Novel synthesis, characterization and magnetic properties of nano-structured γ-Mo2N and γ-Co0.25Mo1.75N nitrides. (February 2017) - Mishra, Pragnya P.; Panda, Rabi N.
Graphical abstract: Highlights: Nano-structured and porous γ-Mo2 N and γ-Co0.25 Mo1.75 N were synthesized. Characterizations were done using XRD, TEM, HRTEM, BET and VSM at 298 K. γ-Mo2 N nano-material possesses high surface area and porosity. γ-Co0.25 Mo1.75 N nano-material possesses moderate surface area and porosity. γ-Mo2 N and γ-Co0.25 Mo1.75 N materials show weak ferro-magnetism. Abstract: Novel synthesis of nano-structured and porous γ-Mo2 N and γ-Co0.25 Mo1.75 N materials have been successfully achieved. The methodologies involve (i) the reaction of metal ions with hydrazine and borohydride resulting MoO3 based procursors and (ii) their subsequent nitridation using NH3 (g) at 700 °C. γ-Mo2 N and γ-Co0.25 Mo1.75 N materials crystallize in fcc structure with lattice parameters, 'a' = 4.193 (±5) Å and 4.198 (±2) Å, respectively. TEM and XRD studies confirm nano-crystalline nature of γ-Mo2 N and γ-Co0.25 Mo1.75 N nitrides having TEM particle sizes of 5 and 12 nm and crystallite sizes of 6 and 11 nm, respectively. HRTEM study confirms lattice stacking and porous structures. BET surface area study indicates high and moderate surface areas for γ-Mo2 N and γ-Co0.25 Mo1.75 N nitride materials, i.e. 53 and 12 m 2 /g, respectively which confirm mesoporous behavior. M vs H plots of γ-Mo2 N and γ-Co0.25 Mo1.75 N materials show weak ferromagnetism having coercivities values of 2838 and 296 Oe, respectively.